Faint source star planetary microlensing: the discovery of the cold gas giant planet OGLE-2014-BLG-0676Lb - Rattenbury, Nicholas James; Tsapras, Yiannis; Giannini, Emanuela; Hundertmark, Markus; Wambsganß, Joachim; Schmidt, Robert W. (Arxiv, 2016)
We report the discovery of a planet --- OGLE-2014-BLG-0676Lb --- via gravitational microlensing. Observations for the lensing event were made by the MOA, OGLE, Wise, RoboNET/LCOGT, MiNDSTEp and $μ$FUN groups. All analyses of the light curve data favour a lens system comprising a planetary mass orbiting a host star. The most favoured binary lens model has a mass ratio between the two lens masses of $(4.78 ± 0.13)× 10^{-3}$. Subject to some important assumptions, a Bayesian probability density analysis suggests the lens system comprises a $3.09_{-1.12}^{+1.02}$ M_jup planet orbiting a $0.62_{-0.22}^{+0.20}$ M_sun host star at a deprojected orbital separation of $4.40_{-1.46}^{+2.16}$ AU. The distance to the lens system is $2.22_{-0.83}^{+0.96}$ kpc. Planet OGLE-2014-BLG-0676Lb provides additional data to the growing number of cool planets discovered using gravitational microlensing against which planetary formation theories may be tested. Most of the light in the baseline of this event is expected to come from the lens and thus high-resolution imaging observations could confirm our planetary model interpretation.